Housing privatization in transition countries: Institutional features and outcomes - Hana M. Broulíková; Josef Montag (Review of Economic Perspectives, 2020)
We provide an overview of housing privatization policies and outcomes in transition economies. Our primary aim is to collect and systematize key information concerning the institutional features of housing privatization in individual countries: we identify the initial conditions, the timeframe of housing privatization and its culmination, the extent of housing privatization, who decided about its terms and conditions, who was entitled to privatize the housing, and at what price. Furthermore, using micro-data covering all transition countries, we present new estimates of the extent of housing privatization, its dynamics during the second half of the 2000s, and the resulting housing tenure structure.
Keywords: P3; R31; P14; 330; Housing privatization; homeownership; economic transition; post-communist economies